Pengaruh Kualitas Pelayanan dan Lokasi Terhadap Kepuasan Konsumen Servis Pada Yamaha Bahana Sukabumi - Alpian Mauludin; Titiek Tjahja Andari; Samsuri Samsuri (Syntax Idea)
This research aims to determine the influence of service quality and location on customer service satisfaction at Yamaha Bahana Sukabumi. The sample in this study was 100 people using a purposive sampling method. The data tested used classical validity, reliability, and assumption test methods. Data analysis techniques use multiple linear regression analysis, multiple correlation analysis, coefficient of determination analysis, f test, and t test. The results of this research show that service quality and location simultaneously or partially have a positive and significant effect on consumer satisfaction.